Supplemental carnitine and exercise - Brass, E. P. (1996)
- Carnitine Metabolism During Exercise - Rationale for use of Carnitine to Enhance Exercise Performance - Considerations in Carnitine Dosing in Normal Humans - Effect of Carnitine Supplementation on Exercise Performance in Normal Humans